Carotenoid crystal formation in Arabidopsis and carrot roots caused by increased phytoene synthase protein levels - Maass, Dirk; Arango, Jacobo; Wüst, Florian; Beyer, Peter; Welsch, Ralf (Public Library of Science, 2009)
As the first pathway-specific enzyme in carotenoid biosynthesis, phytoene synthase (PSY) is a prime regulatory target. This includes a number of biotechnological approaches that have successfully increased the carotenoid content in agronomically relevant non-green plant tissues through tissue-specific PSY overexpression. We investigated the differential effects of constitutive AtPSY overexpression in green and non-green cells of transgenic Arabidopsis lines. This revealed striking similarities to the situation found in orange carrot roots with respect to carotenoid amounts and sequestration mechanism.